CD38 Is Robustly Induced in Human Macrophages and Monocytes in Inflammatory Conditions - Amici, Stephanie A.; Young, Nicholas A.; Narvaez-Miranda, Janiret; Jablonski, Kyle A.; Arcos, Jesus; Rosas, Lucia; Papenfuss, Tracey L.; Torrelles, Jordi B.; Jarjour, Wael N.; Guerau-de-Arellano, Mireia (Frontiers in Immunology, 2018)
Macrophages and their monocyte precursors mediate innate immune responses and can promote a spectrum of phenotypes from pro-inflammatory to pro-resolving. Currently, there are few markers that allow for robust dissection of macrophage phenotype. We recently identified CD38 as a marker of inflammatory macrophages in murine in vitro and in vivo models. However, it is unknown whether CD38 plays a similar marker and/or functional role in human macrophages and inflammatory diseases. Here, we establish that CD38 transcript and protein are robustly induced in human macrophages exposed to LPS (±IFN-γ) inflammatory stimuli, but not with the alternative stimulus, IL-4. Pharmacologic and/or genetic CD38 loss-of-function significantly reduced the secretion of inflammatory cytokines IL-6 and IL-12p40 and glycolytic activity in human primary macrophages. Finally, monocyte analyses in Systemic Lupus Erythematosus (SLE) patients revealed that, while all monocytes express CD38, high CD38 expression in the non-classical monocyte subpopulation is associated with disease. These data are consistent with an inflammatory marker role for CD38 in human macrophages and monocytes.